The effect of job satisfaction and self-efficacy on organizational commitment mediated by organizational culture in generation z age span - Rudy Rudy; Bernard T. Widjaja; Melitina Tecoalu (Institute of Computer Science (IOCS), 2023)
The purpose of this study was to determine the Effect of Job Satisfaction and Self Efficacy on Organizational Commitment Mediated by Organizational Culture in the Age Range of Generation Z. The population in this study was the population of Gojek or Grab couriers in Jabodetabek. and processed using IBM SPSS analysis. Through this research the authors wanted to know the effect of Job Satisfaction, Self-Efficacy, and Organizational Culture on Organizational Commitment. Companies that have a good organizational culture and employees who are satisfied and confident in their own abilities will survive more and generate better profits. Based on the research results obtained empirical facts in the form of: 1) There is no significant effect of Job Satisfaction on Organizational Commitment; 2) There is a significant effect of Self Efficacy on Organizational Commitment; 3) There is no significant influence of Organizational Culture on Organizational Commitment; 4) There is no significant effect of Job Satisfaction on Organizational Culture; 5) There is no significant effect of Self Efficacy on Organizational Culture; 6) Organizational Culture does not have a mediating effect on the influence of Job Satisfaction on Organizational Commitment; 7) Organizational Culture does not have a mediating effect on the influence of Self Efficacy on Organizational Commitment.